2006
DOI: 10.1017/s1431927606060144
|View full text |Cite
|
Sign up to set email alerts
|

Electron Energy Loss Spectroscopy (EELS) of Iron Fischer–Tropsch Catalysts

Abstract: Electron energy loss spectroscopy (EELS), X-ray photoelectron spectroscopy (XPS), and transmission electron microscopy have been used to study iron catalysts for Fischer-Tropsch synthesis. When silica-containing iron oxide precursors are activated in flowing CO, the iron phase segregates into iron carbide crystallites, leaving behind some unreduced iron oxide in an amorphous state coexisting with the silica binder. The iron carbide crystallites are found covered by characteristic amorphous carbonaceous surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 21 publications
4
37
0
Order By: Relevance
“…Due to the mixing of C1s and 3d orbitals (hybridization) of carbon and metal atoms, such a structure also occurs for chromium and iron carbides [57,58]. Due to the superposition of the carbides and metal oxides structures in the NEXAFS C1s X-ray spectra, their study by spectral methods is impossible.…”
Section: Near-edge X-ray Absorption Fine Structure (Nexafs) Spectroscmentioning
confidence: 99%
“…Due to the mixing of C1s and 3d orbitals (hybridization) of carbon and metal atoms, such a structure also occurs for chromium and iron carbides [57,58]. Due to the superposition of the carbides and metal oxides structures in the NEXAFS C1s X-ray spectra, their study by spectral methods is impossible.…”
Section: Near-edge X-ray Absorption Fine Structure (Nexafs) Spectroscmentioning
confidence: 99%
“…The slight increase of intensity that can be seen at energies above the L3 edge is caused by electron scattering processes. The shift indicates the presence of metallic Fe for the oleic acid capped nanoparticles [25,26].…”
Section: Resultsmentioning
confidence: 99%
“…Probing by EELS is a very sensitive technique and very low concentration of elements can be detected. The carbon K-edge structure clearly shows a weak p* shoulder peak and an intense r* peak, which are characteristic of amorphous carbon species [20]. Since the EELS spectra of the rim do not contain any characteristic edge for Fe or oxygen, it can be concluded that the outer rim consists of amorphous carbon only.…”
Section: Morphologymentioning
confidence: 92%
“…High-resolution STEM imaging coupled with EELS analysis was utilized to determine the chemical nature of any particular structure of interest in different catalyst samples mentioned in Table 1. To identify the elemental composition in EELS spectra, characteristic edge structure of Fe (L 2,3 edge at about 720-740 eV), oxygen (K edge at about 530-535 eV) and carbon (K edge at about 285-310 eV) are considered [20].…”
Section: Morphology and Phase Transformation By Hrtem Stem And Eelsmentioning
confidence: 99%